1985
DOI: 10.1121/1.391873
|View full text |Cite
|
Sign up to set email alerts
|

Sound fields near exterior building surfaces

Abstract: Measurement of sound transmission through a building facade requires determination of the incident sound power. Interpretation of sound pressure level measurements near a facade is, however, complicated by interference between the incident sound waves and those reflected from the facade. Experimental data and a simple mathematical model are used to examine systematic effects associated with reflections from a large flat facade and, subsequently, to investigate deviations from this simple situation. Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…levels between -8 and -28 dB) are not always critical in this comparison; these partly depend on the frequency bandwidth or resolution that is chosen for the measurements and predictions. The upper frequency of interest is limited to 1000 Hz because at higher frequencies the turbulent air in the outdoor environment would usually reduce the coherence between the waves travelling along the different propagation paths [4,15]. As a result, the sharp minima in the spectrum due to destructive interference in outdoor measurements near real facades would be less likely to occur above 1000 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…levels between -8 and -28 dB) are not always critical in this comparison; these partly depend on the frequency bandwidth or resolution that is chosen for the measurements and predictions. The upper frequency of interest is limited to 1000 Hz because at higher frequencies the turbulent air in the outdoor environment would usually reduce the coherence between the waves travelling along the different propagation paths [4,15]. As a result, the sharp minima in the spectrum due to destructive interference in outdoor measurements near real facades would be less likely to occur above 1000 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…Below 200 Hz there were significant differences and diffraction effects were noted as one possible cause. Experimental investigations on real facades by Quirt [4] looked at microphone positions on the surface of a façade and at a distance of 2 m from the façade. The results indicated that diffraction fringes were not dominant at measurement positions near corners of a building façade and that the main variations were due to interference effects from the ground surface.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, variations as large as 7 dB were found for a fixed distance from the façade in presence of a recessed window. Briefly, Quirt [6] found that the pressure doubling conditions hold in most of the investigated cases, for all the frequencies, whereas the assumption of energy doubling at 2 m away from a building surface, when appropriate, was reasonable only for one-third octave bands above 100 Hz. The low frequency limit, in his findings, was inversely proportional to the microphone distance from the surface [6].…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…Quirt [6] conducted a study on different incidence conditions using both road sources (outdoor) and a loudspeaker (pure tones of varying frequency, in anechoic room). The author stressed that, in many practical measurement situations, the ''SPL +3 dB'' (energy doubling) and ''SPL + 6 dB'' (pressure doubling) approximations are not appropriate and explicit consideration of the interference effects is required.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation